Comparative outcome assessment of epidermal growth factor receptor tyrosine kinase inhibitors for the treatment of advanced non-small-cell lung cancer: A network meta-analysis - Mello, R (2018)
Introduction: Tyrosine kinase inhibition of the epidermal growth factor receptor (EGFR) is the standard in the first line treatment of patients with advanced nonsmall- cell lung cancer (NSCLC) harbouring EGFR activating mutations. Here we aim to discern efficacy and toxicity measures through a meta-analysis of published studies that could aid treatment selection. Materials And Methods: We performed a meta-analysis of the main randomized clinical trials evaluating the currently approved EGFR-TKIs in first-line of treatment of EGFR-positive advanced NSCLC. Cochrane guidelines were used for statistical analysis. Results: 3,179 patients were included. All EGFR TKIs showed improved outcomes with respect to ORR and PFS when compared to standard platinum-doublet chemotherapy. Comparative ORR for gefitinib, erlotinib and afatinib were 52.1%, 67.3% and 61.6% respectively. HRs for PFS were 0.62 (95% CI, 0.38-1.00) for gefitinib, 0.28 (95% CI, 0.17-0.45) for erlotinib and 0.40 (95% CI, 0.20-0.83) for afatinib. HRs for OS were not statistically significant for any agent. Conclusions: Our results suggest similar clinical efficacy and higher toxicity of Afatinib treatment. As this still remains the agent with best CSF penetration, we suggest its use is limited to patients presenting with brain metastasis. We suggest the use of Gefitinib in patients without CNS involvement. Faced with the impossibility to dose-reduce Gefitinib, Erlotinib represents a tolerable and effective alternative to Afatinib and Gefitinib if response to EGFR inhibition is considered still effective.